Abnormal bleeding in the perimenopausal period - Stetkiewicz, Tomasz; Stachowiak, Grzegorz; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2010)
Abnormal bleeding is a common problem in the perimenopausal period. Abnormal bleeding causes are divided into organic and hormonal. The most important issue in diagnostics of this pathology is exclusion of organic causes, especially of oncologic aetiology. Diagnostics should be based on modern tools such as hysteroscopy, allowing precise imaging and guided biopsy of endometrial tissue. Abnormal bleeding therapy in the perimenopausal period could be operative or conservative, based on hormonal therapy.